Productivity and fruit quality of Jonagold clones of home selection - К. П. Тарнавська (Plant Varieties Studying and Protection)
New results of the clonal selection of apple tree (Malus domestica Borkh) conducted at Podillya Research Station of Horticultural Institute NAAS by method of state variety testing have been presented. By the results of the 6-year studying (2007 - 2012) of 20 new Jonagold clones of domestic selection their estimation was carried out according to the complex of such qualities as productivity, early ripening, marketability, taste qualities and durability of fruits. The following clones are defined to be the best: DP-16, DP-17, DP-18, DP-20. They start fruiting in the age of 2 or 3 years, productivity of the 5- or 6-year-old trees reaches 8,3–25,5 tons per hectare, quantity of the fruits of the highest and first grade is about 57–76% (in 2010–2012). Fruits of the mentioned clones are bigger than medium size (DP-16), big (DP-17, DP-18) and very big (DP-20); they have average similarity, excellent and very harmonious sour-sweet taste (8,3–8,7 points). Fruits of the best clones kept their quality for 202 – 220 days.